Metabolomic approach to explore the chemical composition and health benefits of macroalgae: A comprehensive study of Palmaria palmata, Ascophyllum nodosum, and Chondrus crispus - Natália Čmiková; Milena D. Vukić; Nenad L. Vukovic; Jaroslav Havlík; Hanán Issa-Issa; Ángel A. Carbonell-Barrachina; Ivona Jančo; Vittorio Vinciguerra; Stefania Garzoli; Miroslava Kačániová (Food Chemistry, 2025)

Comparative analysis of SDGs implementation: Testing a novel assessment framework approach - L. Issa; M. El-Fadel (Environmental Impact Assessment Review, 2025)

Clinical and Molecular Profiles of a Cohort of Egyptian Patients with Collagen VI-Related Dystrophy - Wessam E. Sharaf-Eldin; Karima Rafat; Mahmoud Y. Issa; Hasnaa M. Elbendary; Noura R. Eissa; Bahaa Hawaary; Nagwa E. A. Gaboon; Reza Maroofian; Joseph G. Gleeson; Mona L. Essawi; Maha S. Zaki (Journal of Molecular Neuroscience, 2024)
Collagen VI-related dystrophies (COL6-RD) display a wide spectrum of disease severity and genetic variability ranging from mild Bethlem myopathy (BM) to severe Ullrich congenital muscular dystrophy (UCMD) and the intermediate severities in between with dual modes of inheritance, dominant and recessive. In the current study, next-generation sequencing demonstrated potential variants in the genes coding for the three alpha chains of collagen VI ( COL6A1 , COL6A2 , or COL6A3 ) in a cohort of Egyptian patients with progressive muscle weakness ( n = 23). Based on the age of disease onset and the patient clinical course, subjects were diagnosed as follows: 12 with UCMD, 8 with BM, and 3 with intermediate disease form. Fourteen pathogenic variants, including 5 novel alterations, were reported in the enrolled subjects. They included 3 missense, 3 frameshift, and 6 splicing variants in 4, 3, and 6 families, respectively. In addition, a nonsense variant in a single family and an inframe variant in 3 different families were also detected. Recessive and dominant modes of inheritance were recorded in 9 and 8 families, respectively. According to ACMG guidelines, variants were classified as pathogenic ( n = 7), likely pathogenic ( n = 4), or VUS ( n = 3) with significant pathogenic potential. To our knowledge, the study provided the first report of the clinical and genetic findings of a cohort of Egyptian patients with collagen VI deficiency. Inter- and intra-familial clinical variability was evident among the study cohort.

Synthesis of adamantane-monoterpene conjugates with 1,3,4-thiadiazol-2(3H)-imine linker and evaluation of their inhibitory activity against TDP1 - Aldar A. Munkuev; Alexandra L. Zakharenko; Tatyana E. Kornienko; Nadezhda S. Dyrkheeva; Ekaterina S. Ilina; Evgeniy V. Suslov; Fatima Issa; Chigozie Achara; Jóhannes Reynisson; Konstantin P. Volcho; Nariman F. Salakhutdinov; Olga I. Lavrik (Medicinal Chemistry Research, 2024)

Discrimination between hypervirulent and non-hypervirulent ribotypes of Clostridioides difficile by MALDI-TOF mass spectrometry and machine learning - Ahmed Mohamed Mostafa Abdrabou; Issa Sy; Markus Bischoff; Manuel J. Arroyo; Sören L. Becker; Alexander Mellmann; Lutz von Müller; Barbara Gärtner; Fabian K. Berger (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Hypervirulent ribotypes (HVRTs) of Clostridioides difficile such as ribotype (RT) 027 are epidemiologically important. This study evaluated whether MALDI-TOF can distinguish between strains of HVRTs and non-HVRTs commonly found in Europe. Obtained spectra of clinical C. difficile isolates (training set, 157 isolates) covering epidemiologically relevant HVRTs and non-HVRTs found in Europe were used as an input for different machine learning (ML) models. Another 83 isolates were used as a validation set. Direct comparison of MALDI-TOF spectra obtained from HVRTs and non-HVRTs did not allow to discriminate between these two groups, while using these spectra with certain ML models could differentiate HVRTs from non-HVRTs with an accuracy >95% and allowed for a sub-clustering of three HVRT subgroups (RT027/RT176, RT023, RT045/078/126/127). MALDI-TOF combined with ML represents a reliable tool for rapid identification of major European HVRTs.

Effects of citrus pomace on mechanical, sensory, phenolic, antioxidant, and gastrointestinal index properties of corn extrudates - Muhammad Asif; Muhammad Kashif Iqbal Khan; Muhammad Issa Khan; Abid Aslam Maan; Harrison Helmick; Jozef L. Kokini (Food Bioscience, 2023)

Exploratory Study on Lercanidipine Hydrochloride Polymorphism: pH-Dependent Solubility Behavior and Simulation of its Impact on Pharmacokinetics - Ilia Alekseevich Repin; Raimar Loebenberg; John DiBella; António C. L. Conceição; Manuel E. Minas da Piedade; Humberto G. Ferraz; Michele G. Issa; Nadia A. Bou-Chacra; Catharine F. M. Ermida; Gabriel L. B. de Araujo (AAPS PharmSciTech, 2021)

Seismic monitoring and high-frequency noise using arrays in the Arabian Peninsula - Moira L. Pyle; Rengin Gök; Abdullah Al-Amri; Issa El-Hussain; Yasir Al-Rawahi (Arabian Journal of Geosciences, 2020)

Anticoccidial effects of Khaya senegalensis aqueous stem bark extract on broiler chickens experimentally infected with Eimeria species - Issa A. Muraina; Jurbe G. Gotep; James T. Tanko; ThankGod E. Onyiche; Oladimeji B. Aladelokun; Christiana C. Dapuliga; Gilead E. Forcados; Nonyelim Ozele; Ann L. Samuel; Olusola O. Oladipo; Olatunde B. Akanbi; Philip A. Okewole; et al. (Tropical Animal Health and Production, 2020)

Biofilms grown in aquatic microcosms affect mercury and selenium accumulation in Daphnia - Semona Issa; Tomasz Maciej Ciesielski; Øyvind Mikkelsen; Sigurd Einum; Veerle L. B. Jaspers (Ecotoxicology, 2020)
Experiments examining mercury (Hg) toxicity in Daphnia are usually conducted in highly standardized conditions that prevent the formation of biofilm. Although such standardization has many advantages, extrapolation of results to natural conditions and inference of ecological effects is challenging. This is especially true since biofilms can accumulate metals/metalloids and play a key role in their transfer to higher trophic level organisms. In this study, we experimentally tested the effects of spontaneously appearing biofilm in Daphnia cultures on accumulation of Hg and its natural antagonist selenium (Se) in Daphnia magna . We added Hg (in the form of mercury (II) chloride) at two concentrations (0.2 µg/L and 2 µg/L) to experimental microcosms and measured the uptake of Hg and Se by D. magna in the presence and absence of biofilm. To test for consistent and replicable results, we ran two identical experimental sets one week apart. Biofilm presence significantly reduced the accumulation of Hg, while increasing the tissue Se content in D. magna , and these findings were reproducible across experimental sets. These findings indicate that highly standardized tests may not be adequate to predict the bioaccumulation and potential toxicity of metals/metalloids under natural conditions.

Chironomus sancticaroli (Diptera, Chironomidae) as a Sensitive Test Species: Can We Rely on Its Use After Repeated Generations, Under Laboratory Conditions? - Juliano J. Corbi; Aline C. Bernegossi; Lidia Moura; Mayara C. Felipe; Carina G. Issa; Mara Rubia L. Silva; Guilherme R. Gorni (Bulletin of Environmental Contamination and Toxicology, 2019)

Naringenin mitigates titanium dioxide (TiO2)-induced chronic arthritis in mice: role of oxidative stress, cytokines, and NFκB - Marília F. Manchope; Nayara A. Artero; Victor Fattori; Sandra S. Mizokami; Dimitrius L. Pitol; João P. M. Issa; Sandra Y. Fukada; Thiago M. Cunha; José C. Alves-Filho; Fernando Q. Cunha; Rubia Casagrande; Waldiceu A. Verri (Inflammation Research, 2018)

Variation of hydrogeochemical characteristics of water in surface flows, shallow wells, and boreholes in the coastal city of Douala (Cameroon) - Wilson Y. Fantong; Brice T. Kamtchueng; Beatrice Ketchemen-Tandia; Doris Kuitcha; Josephine Ndjama; Alain T. Fouepe; Gloria E. Takem; Issa; Mengnjo J. Wirmvem; Serges L. Bopda Djomou; Andrew A. Ako; George E. Nkeng; et al. (Hydrological Sciences Journal, 2016)

Analysing the relationship between land units and plant communities: The case of Socotra Island (Yemen) - F. Attorre; A. Issa; L. Malatesta; A. Adeeb; M. De Sanctis; M. Vitale; A. Farcomeni (Plant Biosystems, 2014)

Resistance mechanism to the pod-sucking bug Clavigralla tomentosicollis (Hemiptera: Coreidae) in the cowpea IT86D-716 variety - Clementine L. Dabire-Binso; Niango Malick Ba; Antoine Sanon; Issa Drabo; Kouahou Foua Bi (International Journal of Tropical Insect Science, 2010)

Nostoc cyanobacterial inoculation in South African agricultural soils enhances soil structure, fertility, and maize growth - M. P. Maqubela; P. N. S. Mnkeni; O. Malam Issa; M. T. Pardo; L. P. D’Acqui (Plant and Soil, 2009)

Molecular mechanism of vitamin D receptor action - L. L. Issa; G. M. Leong; J. A. Eisman (Inflammation Research, 1998)